Formation process and oxidation behavior of MCrAlY + AlSiY composite coatings on a Ni-based superalloy. (1st September 2022) - Li, S.M.; Fu, L.B.; Zhang, W.L.; Li, W.; Sun, J.; Wang, T.G.; Jiang, S.M.; Gong, J.; Sun, C.
Highlights: An AlSiY coating and two MCrAlY + AlSiY composite coatings with different thickness of MCrAlY interlayer were prepared by arc ion plating and subsequent vacuum annealing. The addition of MCrAlY layer, to some extent, prevented the diffusion of refractory elements to the outer layer. The higher the Si content in the outer layer, the stronger the inhibition of Al inward diffusion. Abstract: An AlSiY coating and two MCrAlY + AlSiY composite coatings with different thickness of MCrAlY interlayer were prepared by arc ion plating (AIP) and vacuum annealing. The isothermal oxidation behavior of coatings at 1100 °C for 300 h was also investigated to characterize the microstructure evolution of coatings during annealing. The composite coatings exhibited a better high-temperature oxidation resistance at 1100 °C. The reason is that the addition of MCrAlY layer can greatly contribute to prevent the diffusion of refractory elements to the outer layer. The inhibition of Al inward diffusion can be much stronger, as the Si content increases in the outer layer during annealing.